Can the Interdependence Effect and the Contagion Phenomena be Related with One Another? - Korkmaz, Abdurrahman (Journal of Empirical Studies, 2014)
This study suggests an alternative approach to the transmission process of financial crises across emerging economies. This paper hypothesizes that the interdependence effect could become weaker, disappears completely or swerves during the crisis period due to the contagion phenomenon. The hypothesis put forward in this paper is of great importance in terms of policy implications inasmuch as it is supported by the data for many cases.